REVITALISASI NILAI-NILAI KEBHINEKAAN KEPADA FORUM ANAK KOTA PASURUAN MELALUI DISEMINASI MEDIA SOSIAL - Khamdan Safiudin (An-Nas, 2022)
Preventive efforts in realizing a harmonious life in society, especially among children with an attitude of diversity, can apply one strategy that can be tried, namely through the use of digital literacy through social media dissemination to Pasuruan city children who are members of the children's forum platform membership. Quantitative research is used in this type of study, survey research is the method used. Through the survey method, this research was conducted in an effort to reveal the attitudes and understanding of Pasuruan city's children's forum towards the values of diversity through digital literacy (social media dissemination). The presentation of the research results describes the profile of the Pasuruan City Children's Forum, in particular the behavior and social interactions of the Pasuruan city children's forum itself, and a portrait of the values diversity in structure of social strata the community. Based on data reduction, the research results are classified into two findings. First, the behavior and social interaction of the children's forum on the use of digital literacy and second, the portrait of the values of the diversity of the children's forum in Pasuruan. The behavior and interaction of children's forums in the city of Pasuruan shows that they are digitally literate and actively use social media, social media has advantages and practical values in its use in instilling the values of diversity. The existence of social media hasdirectedchildren's behavior and social interactions to online behavior. Children's forums are depicted in their behavior and interactions through social media and there are some information content on the values of diversity that are instilled by the community. Among them are reading, searching or research, responding and then following up, and finally spreading it.